How I rob banks : (and other such places) - F. C. (John Wiley & Sons, 2023)
Follow FC as he steals from the world's most secure banks and government facilities--without breaking a single law In How I Rob Banks: And Other Such Places, renowned ethical hacker and social engineer FC delivers a gripping and often hilarious discussion of his work: testing the limits of physical bank security by trying to "steal" money, data, and anything else he can get his hands on. In the book, you'll explore the secretive world of physical assessments and follow FC as he breaks into banks and secure government locations to identify security flaws and loopholes. The author explains how banks and other secure facilities operate, both digitally and physically, and shows you the tools and techniques he uses to gain access to some of the world's most locked-down buildings. You'll also find: Strategies you can implement immediately to better secure your own company, home, and data against malicious actors Detailed photos, maps, and drawings to bring to life the unbelievable true stories contained inside An inside and candid look at a rarely examined industry through the eyes of one of its most respected penetration testers A can't-miss account of real-life security exploits perfect for infosec pros, including red and blue teamers, pentesters, CIOs, CISSPs, and social engineers, How I Rob Banks also belongs in the hands of anyone who loves a great Ocean's 11-style story pulled straight from the real world.